A Role for Insulin in Diabetic Neuropathy - Grote, Caleb W.; Wright, Douglas E. (Frontiers in Neuroscience, 2016)
Abstract The peripheral nervous system is one of several organ systems that are profoundly affected in diabetes. The longstanding view is that insulin does not have a major role in modulating neuronal function in both central and peripheral nervous systems is now being challenged. In the setting of insulin deficiency or excess insulin, it is logical to propose that insulin dysregulation can contribute to neuropathic changes in sensory neurons. This is particularly important as sensory nerve damage associated with prediabetes, type 1 and type 2 diabetes is so prevalent. Here, we discuss the current experimental literature related to insulin’s role as a potential neurotrophic factor in peripheral nerve function, as well as the possibility that insulin deficiency plays a role in diabetic neuropathy. In addition, we discuss how sensory neurons in the peripheral nervous system respond to insulin similar to other insulin-sensitive tissues. Moreover, studies now suggest that sensory neurons can also become insulin resistant like other tissues. Collectively, emerging studies are revealing that insulin signaling pathways are active contributors to sensory nerve modulation, and this review highlights this novel activity and should provide new insight into insulin’s role in both peripheral and central nervous system diseases.